THE EVALUATION OF INTERNAL CONTROL ELEMENTS IN THE QUALITY MANAGEMENT SYSTEM OF EDUCATION ESTABLISHMENTS AT LAW ENFORCEMENT INSTITUTIONS - Zālītis, Ivars; Davidova, Jeļena; Ignatjeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Under the conditions of a growing competition in the field of educational services and the increasing demands of the labor market for well-educated and highly qualified workforce, the quality of professional efficiency assumes a particular significance. Taking into consideration the present situation concerning the security of the EU borders and problems created by the migration as well as the challenges they pose, the quality management systems and their effectiveness are vital also for educational institutions training specialists for the needs of the departments of the Ministry of the Interior. The research is aimed at establishing the most effective principles for working out the quality management system of vocational training in regard to one of the basic elements of the quality system: the resource of internal quality in an educational institution. The paper reflects and provides the analysis of the research process and outcomes that have been obtained from the interviews conducted among twenty Baltic State experts in the field of professional training of border guards and police employees, and by evaluating the resources and elements of quality management system according to the criterion “Impact on the study process quality”. The obtained research and empirical data provide scientifically valid frame for the actions of education establishments of law enforcement institutions on defining the principles at working out the quality management system.